Influence of Surface Roughness on Durability of New-Old Concrete Interface - Nurdeen Mohamed Altwair; Younis Omran Yacoub; Abdualhamid Mohamed Alsharif; Lamen Saleh Sryh (Advances in Technology Innovation, 2024)
The bond zone between old and new concrete is greatly affected by environmental factors. This study investigates the impact of surface roughness on durability using as-cast surface (CS), drilled holes surface (DS), and grooved surface (GS). After a 28-day water-curing, specimens undergo a 5% NaCl solution immersion for 30 and 60 days; exposure to temperatures of 200 ℃ and 500 ℃; and a water permeability test. Slant shear and splitting tensile tests assess durability. Results show that CS exhibits the greatest decrease in resistance to sodium chloride solution and temperature, while DS and GS show less pronounced effects. At 500 ℃, CS and DS specimens fail, whereas GS retains 50% and 75% of its shear and tensile strengths, respectively. GS has the lowest water permeability (7 × 10-11 m/s), followed by DS (1.2 × 10-10) and CS (1.5 × 10-10). Overall, surface roughness enhances durability and mitigates environmental effects.